Understanding the role of loyalty dimensions and their impact on customer retention - Dwivedi, Sunita; Tajdini, Javad; Baswan, Taru; Pillai, Pradeep Kumar (Inderscience Enterprises Ltd, 2024)
This study compares the impact of the following two dimensions of loyalty (behavioural and attitudinal) on customer retention in online shopping platforms. Further research also aims to determine whether the brand image plays a critical role in accelerating the impact of these dimensions (behavioural/attitudinal) of loyalty on customer retention for online shopping platforms or not. In the research, primary data represent the respondent from Delhi NCR. The author applied respondents' demographic profiles and brand image as the controlled variable in this research. The study's findings were exciting, showing that attitudinal loyalty significantly enforces customer retention over behavioural loyalty, and the presence of brand image fosters the impact of loyalty on retention. This study also concludes that age, gender, and qualification do not significantly correlate or impact customer retention. Results of the study suggest that attitude is essential in driving customer retention.
Keywords: customer loyalty; behavioural loyalty; attitudinal loyalty; customer retention; online shopping platforms